Implementation of Internet of Things (IoT) Technology in Air Pollution Monitoring in Jakarta: Quantitative Analysis of the Influence of Air Quality Change and Its Impact on Public Health in Jakarta - Arief Budi Pratomo; Hanifah Nurul Muthmainah; Natal Kristiono; Gogor Christmass Setyawan (Westscience Press, 2023)
Air pollution is a pressing global issue, particularly in urban areas where rapid industrialization and urbanization have led to deteriorating air quality. Jakarta, as one of the world's most populous megacities, faces significant challenges in managing air pollution and safeguarding public health. This research paper explores the implementation of Internet of Things (IoT) technology for air pollution monitoring in Jakarta and quantitatively assesses the influence of air quality changes on public health outcomes. The study involves the deployment of IoT sensors to collect real-time data on key air pollutants, including particulate matter (PM2.5, PM10), nitrogen dioxide (NO2), sulfur dioxide (SO2), carbon monoxide (CO), and ozone (O3). Statistical analyses, including regression and correlation analyses, reveal strong associations between air quality variables and health indicators. Findings indicate that elevated levels of PM2.5 and NO2 are linked to increased hospital admissions for respiratory diseases, and CO levels are associated with hypertension and cardiovascular diseases. The study also explores public perception through surveys and questionnaires, highlighting a high level of awareness and support for government initiatives to improve air quality. The results emphasize the need for informed policy decisions, including stricter emission standards and public awareness campaigns, to combat air pollution and protect public health in Jakarta.